Letter (copy) : Help for Spain - Citrine, Walter, 1887-1983
030-0038-001 Secretary' s. WMC/FC/EK/110. 10th October, 1938. Senor Francisco Dalmau, Apartado No. 2, BARCELONA. Dear Sir, HELP FOR SPAIN. I desire to thank you for your letter of the 11th September and have carefully noted the suggestion you make. I am not quite clear in regard to certain details of the scheme and whilst I cannot see that we can dispose of the quantities you suggest, before any decision could be taken it would be necessary to have particulars:- (1) As to whether there would be any difficulty with the Spanish Government, as I understand wine supplies are rationed in the country; (2) Who would be responsible for freight charges? and (3) Is it proposed that if any scheme could be agreed upon, the wine would be landed in London free of cost? I should be glad if you could talk the matter over with our representative in Barcelona, Senor Enrique Santiago, Aragaon 300. Yours faithfully, General Secretary. 292/946/30/38